A single cis-2 regioisomer of ethylene-tethered indene dimer–fullerene adduct as an electron-acceptor in polymer solar cells1. Issue 39 (14th May 2015) - Tao, Ran; Umeyama, Tomokazu; Higashino, Tomohiro; Koganezawa, Tomoyuki; Imahori, Hiroshi
<x xml:space="preserve">Abstract</x> A single cis-2 isomer of fullerene bis-adduct has been synthesized, isolated and applied as an electron-acceptor in polymer solar cells.